EFEK LIKUIDITAS DAN CAPITAL INTENSITY TERHADAP AGRESIF PAJAK MELALUI INTELLECTUAL CAPITAL - Sulfati, Andi Sulfati; Sulfahmi , Andi Alfiyyah Suci Sulfahmi; Amin, Asbi (Journal of Economic, Public, and Accounting (JEPA), 2024)
Tax aggressiveness is a practice carried out by taxpayers to aggressively reduce their tax obligations by utilizing loopholes in tax law either legally or not. The purpose of this study was to determine how liquidity and capital intensity affect tax aggressiveness through intellectual capital as a mediating variable. The population taken is companies listed on the LQ45 Index on the IDX. The sample selection method used purposive sampling method so that 45 companies were obtained for 3 years (2020-2022). The results found that liquidity and intellectual capital have no significant effect on aggressive taxation. Capital intensity has a significant effect on tax aggression. Liquidity and capital intensity have a significant effect on intellectual capital. However, liquidity and capital intensity do not have a significant effect on tax aggressiveness through intellectual capital.